Analysis Of The Implementation Program For Acceleration Of Stunting Reduction In The Work Area Of Ujoh Bilang Community Health Center, Mahakam Ulu Regency - Nordianiwati; Ribka Bibiana Heom (Journal of Innovative and Creativity, 2025)
The stunting rate at the Ujoh Bilang Health Centre in 2020 was 60 toddlers; in 2021 it dropped to 30 toddlers, and in 2022 the stunting rate dropped to 13 toddlers. In the implementation of the stunting programme at the Ujoh Bilang Health Centre, it is still not running optimally, as seen from the information aspect, the availability of local PMT infrastructure facilities, and the attitude of the implementers. This study is to find out the implementation of the decline acceleration programme at the Ujoh Bilang Health Centre from the perspective of information, the availability of local PMT infrastructure facilities, and the attitude of the implementers. This study uses a qualitative method with a case study approach. In-depth interview, observation, and documentation techniques. A and 6 informants, namely 1 Head of the Health Centre, 1 Head in Charge of the Stunting Programme, 1 Midwife of the Ujoh Bilang Health Centre, 1 Posyandu Cadre, 1 pregnant woman, and 1 mother under five. The results of this study found that information and education in the implementation of the Acceleration Programme in the work area of the Ujoh B Ilang Health Centre were not good enough. The availability of PMT is already good because of the funds available, which are given in the form of food, such as milk, eggs, cooking oil, sugar, green beans, and peanuts, and then in the form of snacks and main meals. The attitude of the implementers in the implementation of the stunting programme in the work area of the Ujoh B Ilang Health Centre has been well demonstrated to the community. It can be concluded that for the delivery of information, it is hoped that the Puskesmas can carry out the programmeme according to the time stated in the programmeme implementation information. Then it is hoped that the Puskesmas also needs to pay attention to the obstacles to delivery with villages that have limited access due to the location of long coverage and limited networks; it is hoped that the Puskesmas can further increase cooperation with the village to find solutions related to the obstacles experienced together. For the provision of additional food (PMT), it is hoped that the organisers can continue to monitor for people who have not received the distribution. If there are people who do not participate in the programme, it is hoped that the organisers, both Puskesmas and Posyandu cadres, can find out and distribute the PMT. Regarding the attitude of the implementers, it is hoped that the Puskesmas can maintain and increase a positive and responsive attitude to the community, especially the target of the programmeme, so that they are more enthusiastic about participating in the programmeme.